2019
DOI: 10.35622/j.rie.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Estilos de aprendizaje y los desempeños académicos del área de comunicación en los estudiantes de educación básica

Abstract: La investigación consistió en determinar la relación entre estilos de aprendizaje y el desempeño académico en el área de Comunicación en estudiantes de la institución educativa "Carlos Rubina Burgos" de Puno, 2017. Fue de tipo básico, con diseño no experimental transeccional descriptivo – correlacional. 63 estudiantes constituyeron la muestra censal. Se utilizó las técnicas: encuesta y la observación sistemática indirecta, el instrumento fue el Cuestionario Honey-Alonso de Estilos de Aprendizaje (CHAEA) consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…However, the results obtained by Martínez (2002) indicate that teachers have not yet become familiar with learning styles in their pedagogical work. Therefore, a quality of learning is not guaranteed (Yana et al, 2019), research results that coincide with those found.…”
Section: -145mentioning
confidence: 62%
See 1 more Smart Citation
“…However, the results obtained by Martínez (2002) indicate that teachers have not yet become familiar with learning styles in their pedagogical work. Therefore, a quality of learning is not guaranteed (Yana et al, 2019), research results that coincide with those found.…”
Section: -145mentioning
confidence: 62%
“…Thus, they are teaching preferences and behaviors usually exhibited in the teaching activity and abstracted from the academic and professional experience, taking learning styles as a reference (Martínez, 2002). However, university teachers have not yet managed to become habitually familiar with these learning styles, so the development of each style continues to occur at low levels and does not guarantee educational quality (Yana et al, 2019).…”
Section: -145mentioning
confidence: 99%
“…Sin embargo, los resultados obtenidos por Martínez (2002) indican que los docentes aún no se han familiarizado con los estilos de aprendizaje en su labor pedagógica. Por tanto, no se garantiza una calidad de aprendizaje (Yana et al, 2019), resultados de investigación que coinciden con los encontrados.…”
Section: Discussionunclassified
“…Son preferencias y conductas docentes que se suelen exhibir en la actividad docente y que se han abstraído de la experiencia académica y profesional, tomando como referencia los estilos de aprendizaje (Martínez, 2002). Sin embargo, los docentes universitarios aún no han logrado familiarizarse habitualmente con estos estilos de aprendizaje, por lo que el desarrollo de cada estilo sigue ocurriendo en niveles bajos y no garantiza la calidad educativa (Yana et al, 2019).…”
Section: Introductionunclassified